2005
DOI: 10.1192/bjp.187.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antisocial behaviour, attention-deficit hyperactivity disorder and maternal prenatal smoking

Abstract: Both antisocial behaviour and ADHD symptoms in offspring are independently influenced by maternal prenatal smoking during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 21 publications
5
79
0
2
Order By: Relevance
“…and "How many cigarettes/day did you smoke whilst pregnant?" These questions are similar to those found in most other assessment instruments (e.g., the Centers for Disease Control and Prevention Pregnancy Risk Assessment Monitoring System Questionnaire; see Beck et al, 2002) and like those found in most other studies (particularly those assessing large samples, e.g., Button et al, 2005;Fergusson et al, 1998;Maughan et al, 2004;Wakschlag & Hans, 2002). Because amount of cigarettes reportedly smoked tends to be a "rounded" number, for example, 5, 10, 15, and so forth, mothers were classified into one of three groups (0, 1-9, ≥10 cigarettes/ day).…”
Section: Maternal Prenatal Smokingsupporting
confidence: 77%
“…and "How many cigarettes/day did you smoke whilst pregnant?" These questions are similar to those found in most other assessment instruments (e.g., the Centers for Disease Control and Prevention Pregnancy Risk Assessment Monitoring System Questionnaire; see Beck et al, 2002) and like those found in most other studies (particularly those assessing large samples, e.g., Button et al, 2005;Fergusson et al, 1998;Maughan et al, 2004;Wakschlag & Hans, 2002). Because amount of cigarettes reportedly smoked tends to be a "rounded" number, for example, 5, 10, 15, and so forth, mothers were classified into one of three groups (0, 1-9, ≥10 cigarettes/ day).…”
Section: Maternal Prenatal Smokingsupporting
confidence: 77%
“…Genetic risk for antisocial behavior may contribute to a mother's likelihood of SDP and may confer vulnerability to externalizing problems when inherited by offspring. Standard correlational (Button, Thapar, & McGuffin, 2005;Knopik et al, 2005;Maughan, Taylor, Caspi, & Moffitt, 2004;Thapar et al, 2003) have used an approach, including a measure of SDP in a standard twin study, that assumes the relation is purely environmental (Purcell & Koenen, 2005;Turkheimer, D'Onofrio, Maes, & Eaves, 2005). Therefore, previous studies have been unable to explore the possibility that passive rGE accounts for observed relations between SDP and externalizing.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Standard correlational research approaches, in which environmental and genetic risks are confounded, are ineffective in delineating whether associations between externalizing problems and SDP are due to environmental causation or passive rGE (D'Onofrio et al, 2003;Moffitt, 2005;Rutter, Pickles, Murray, & Eaves, 2001). Moreover, most of the genetically informed studies of SDP and externalizing problems in offspring (Button, Thapar, & McGuffin, 2005;Knopik et al, 2005;Maughan, Taylor, Caspi, & Moffitt, 2004;Thapar et al, 2003) have used an approach, including a measure of SDP in a standard twin study, that assumes the relation is purely environmental (Purcell & Koenen, 2005;Turkheimer, D'Onofrio, Maes, & Eaves, 2005). Therefore, previous studies have been unable to explore the possibility that passive rGE accounts for observed relations between SDP and externalizing.…”
mentioning
confidence: 99%
“…The strength of association does differ slightly between studies, although generally it appears that the children of smokers are approximately 1.5-3 times more likely to have ADHD or ADHD symptoms than the children of non-smokers. Some studies which analyzed ADHD symptoms based on Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria or DuPaul Rating Scale indicate the statistically significant association with the exposure to tobacco smoke [58,[60][61][62][63][64]. In opposite, the results from Hill et al [65], Nigg et al [66], Thapar et al [67] and Lavigne et al [68] were not statistically significant.…”
Section: Ijomeh 2012;25(4) 336mentioning
confidence: 99%